2018
DOI: 10.1177/2325967117750104
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Factors Affecting Healing, Range of Motion, Strength, and Patient-Reported Outcomes After Arthroscopic Rotator Cuff Repair

Abstract: Background:Rotator cuff repair (RCR) leads to improved patient outcomes, which may or may not coincide with biological healing of the tendon. Many patient factors may play a role in subjective and objective patient outcomes of surgery.Purpose:To evaluate the effect of various patient factors and tendon healing on range of motion, strength, and functional outcomes after arthroscopic RCR.Study Design:Case-control study; Level of evidence, 3.Methods:We reviewed patients who underwent arthroscopic RCR. Postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
2
28
0
2
Order By: Relevance
“…All patients had a preoperative cumulative Goutallier grade of ≥3. 47 Nineteen of 22 patients (86.4%) had a preoperative GFMDI of ≥2. 10 On 6-month MRI, 2 of 22 patients (9.1%) had a superior capsular graft tear (Figure 2).…”
Section: Resultsmentioning
confidence: 96%
“…All patients had a preoperative cumulative Goutallier grade of ≥3. 47 Nineteen of 22 patients (86.4%) had a preoperative GFMDI of ≥2. 10 On 6-month MRI, 2 of 22 patients (9.1%) had a superior capsular graft tear (Figure 2).…”
Section: Resultsmentioning
confidence: 96%
“…There is literature that clearly supports improvement in factors such as patient reported functional outcomes, pain, strength, and range of motion after common shoulder surgeries like rotator cuff repair, total shoulder arthroplasty, and reverse total shoulder arthroplasty (18)(19)(20). Having said that, not all patients are created equal when it comes to predicting outcomes after surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the characteristics of the pathology in question can impact surgical success rates. For example, Wylie et al found that patients with multiple tendon tears, tears >2.2 cm, and retraction >2.0 cm were less likely to heal following arthroscopic rotator cuff repair (18). Even more so, as health care has moved away from a paternalistic physician-patient relationship and increasingly moves toward shared decision-making between providers and patients alike, many patients will simply choose not to proceed with a surgery or procedure (21).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that tear severity (size, retraction) is not correlated with the clinical expression of rotator cuff tearing whereas mental health had the strongest correlation of any factor with baseline outcomes and was strongly associated with functional outcomes after repair. 2,3 Similarly, the decision of a patient to undergo repair versus nonoperative treatment for a chronic rotator cuff tear has very little to do with the anatomy of the tear but rather is most influenced by low patient expectations regarding the effectiveness of physical therapy. 4 Consequently, psychosocial factors including patient expectations and mental well-being likely have a tremendous influence on the clinical expression of rotator cuff tearing, the decisions to pursue treatments, and the outcomes of those treatments.…”
mentioning
confidence: 99%